AB1045 Development and Validation of Juvenile Autoinflammatory Disease Multidimensional Assessment Report (JAIMAR). (10th June 2014) - Konukbay, D.; Yildiz, D.; Acikel, C.; Sozeri, B.; Makay, B.; Ayaz, N.; Barut, K.; Kisaarslan, A.; Bilginer, Y.; Peru, H.; Erdogan, O.; Unsal, E.; et al.
Abstract : Background: There are a lot of effects of auto-inflammatory diseases (e.g. fear of attack, pain, fever, fatigue, problems at school) that are quite important to patients but have not been measured with the outcome instruments currently included in clinical trials of autoinflammatory diseases. Objectives: The aim of this study is to develop and test a new multidimensional questionnaire for assessment of children with autoinflammatory disease (AID) in standard clinical care. Methods: JAIMAR includes 16 parent or patient - centered measures and four dimensions that assess functional status, pain, therapeutic compliance and health-related quality of life with disease outcome. The JAIMAR is proposed for use as both a proxy-report and a patient self-report, with the suggested age range of 7-18 years for use as a self-report. The study was conducted in children with AID and their parents in seven different paediatric rheumatology center from Turkey. To validate the JAIMAR, the Outcome Measures in Rheumatology Clinical Trials (OMERACT) filter for outcome measures in rheumatology was applied. Results: Completion and scoring appeared to be quick, requiring avarage15 minutes. The analysis data set included by the parents of 250 children with FMF in 351 visits and by 179 children in 187 visits. The median age of the children was 10.64±4.38 and female to male ratio was. The JAIMAR was found to be feasible and to possess face, content, criterion and construct validity. The cronbach's alpha coefficient for internal consistency for the JAIMAR dimensions were between for parents 0.677-0.998 and for children 0.507-0.986. Parents' proxy-reported and children's self-reported data were outstandingly concordant.The JAIMAR dimensions patient self-report and parent proxy-report cronbach's alpha values were between 0.770-0.989. Conclusions: The development of the JAIMAR introduces a new and multi-dimensional approach in pediatric rheumatology practice. The JAIMAR provided thorough information for the study patients about recent medical history, attack status and current health status. It is valid tool for children with autoinflammatory disease and will help enhance the quality of care of in this group of patients References: Kalkan G, Demirkaya E, Acikel CH, Polat A, Peru H, Karaoglu A, Sari E, Dursun I, Gok F, Ozen S; (FAVOR). Evaluation of the current disease severity scores in paediatric FMF: is it necessary to develop a new one? Rheumatology (Oxford). 2012, 51(4):743-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5963